Tinjauan Siyasah Tanfidziyyah terhadap Praktik Penutupan Jalan untuk Kepentingan Sosial Berdasarkan Undang-Undang Nomor 22 Tahun 2009 - Istiqomah Vatriana; Marwin; Hendriyadi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study examines the practice of road closures for social purposes from the perspective of siyasah tanfidziyyah within the framework of Law Number 22 of 2009 on Road Traffic and Transportation. The government plays an executive role through policy formulation, infrastructure planning, traffic management, and public education. However, several challenges remain, including low public legal awareness, inadequate supporting infrastructure, weak law enforcement, and limited coordination among relevant stakeholders. From the perspective of Islamic governance, the implementation of executive authority (al-sulthan al-tanfidziyyah) reflects the principles of siyasah syar’iyyah, which emphasize public welfare (maslahah ‘ammah) and social order. The findings indicate that although regulatory implementation has been initiated, improvements in governance effectiveness, law enforcement consistency, and public participation are still required to ensure legal certainty and sustainable traffic management. Strengthening institutional capacity and integrating normative legal frameworks with Islamic governance values are essential to optimize the management of road closure practices for social interests.